Noninvasive diagnostic techniques in the preoperative setting of Mohs micrographic surgery: A review of the literature. Issue 11 (23rd September 2022) - Venturi, Federico; Pellacani, Giovanni; Farnetani, Francesca; Maibach, Howard; Tassone, Daniela; Dika, Emi
Abstract: Mohs micrographic surgery (MMS) is considered the gold standard treatment for skin cancers. Though the high cure rates it offers, MMS presents some disadvantages, as it is a relatively time‐consuming procedure involving several professionals (physicians and technicians). A better definition of tumor margins in the preoperative setting with any optical noninvasive diagnostic method may reduce the numbers of MMS steps and the overall duration of the procedure. The present review was conducted and reported using validated search strategies from the following databases: PUBMED and Ovid MEDLINE. Our review describes the use of procedures such as dermoscopy, optical coherence tomography, reflectance confocal microscopy and fluorescent confocal microscopy to determine tumor extension in the preoperative setting of Mohs surgery for the treatment of skin cancers. Presurgical margin assessment with noninvasive diagnostic techniques seem to provide a benefit in the patients' management, especially for tumors located in critical areas with a high risk of recurrence. The use is limited to the high costs and limited availability of new technologies.